Nonsteroidal Anti-Inflammatory Drugs Promote Axon Regeneration via RhoA Inhibition - Fu, Qiao (J Neurosci, 2007)
After a CNS injury in the adult mammals, axonal regeneration is very limited because of the reduced intrinsic growth capacity and nonpermissive environment for axonal elongation. The growth inhibitions from CNS myelin and astroglial chondroitin sulfate proteoglycans partially account for the lack of CNS repair. Here, we show that the nonsteroidal antiinflammatory drugs (NSAIDs) ibuprofen and indomethacin, the drugs widely used as pain relievers in the clinic, can surmount axon growth restrictions from myelin and proteoglycans by potently inhibiting their downstream pathway RhoA signal. Similar to Rho and Rock inhibitors C3 transferase or Y27632 [(R)-(+)-trans-N-(4-pyridyl)-4-(1-aminoethyl)-cyclohexanecarboxamide], both NSAID drugs stimulate a significant neurite growth in the cultured dorsal root ganglion neurons exposed to the inhibitory substrates. Systemic administration of ibuprofen to spinal cord-lesioned rodents reverses the active RhoA signal around injury area measured via Rho-GTP binding assay. Subcutaneous injections of ibuprofen via minipumps to rats with a thoracic spinal cord transection or contusion injury result in substantial corticospinal and serotonergic axon sprouting in the caudal spinal cord and promote locomotor functional recovery, even delaying the treatment 1 week after trauma. In contrast, the non-RhoA-inhibiting NSAID naproxen does not have the axon growth-promoting effects on cultured or lesioned neurons. These studies demonstrate the therapeutic potential of RhoA-inhibiting NSAIDs in treating CNS injuries characterized by axonal disconnection including spinal cord injury.